The impact of immune checkpoint therapy on the latent reservoir in HIV-infected individuals with cancer on antiretroviral therapy. (1st August 2021) - Lau, Jillian S.Y.; McMahon, James H.; Gubser, Celine; Solomon, Ajantha; Chiu, Chris Y.H.; Dantanarayana, Ashanti; Chea, Socheata; Tennakoon, Surekha; Zerbato, Jennifer M.; Garlick, Jill; Morcilla, Vincent; Palmer, Sarah; et al.
Abstract : Objective: The aim of this study was to quantify HIV-specific immunological and virological changes in people with HIV (PWH) on antiretroviral therapy (ART) with malignancy who received immune checkpoint blockade (ICB). Design: An observational cohort study. Methods: Blood samples were collected before and after four cycles of ICB in HIV-positive adults on ART. Virological assessments performed on CD4 + T cells included cell-associated unspliced HIV RNA, cell-associated HIV DNA, Tat/rev-induced limiting dilution assay (TILDA) and plasma HIV RNA using a single copy assay (SCA). Flow cytometry was used to assess the frequency of precursor exhausted T cells (Tpex) and exhausted T cells (Tex), and Gag-specific CD4 + and CD8 + T cells positive for IFN-γ, TNF-α or CD107a by intracellular cytokine staining (ICS). Results: Participant (P)1 received avelumab (anti-PD-L1) for Merkel cell carcinoma. P2 and P3 received ipilimumab (anti-CTLA-4) and nivolumab (anti-PD-1) for metastatic melanoma. An increase in CA-US RNA following each infusion was noted in all three participants. There were no consistent changes in HIV DNA or the proportion of cells with inducible MS HIV RNA. P2 demonstrated a striking increase in the frequency of gag-specific central and effector memory CD8 + T cells producing IFN-γ, TNF-α and CD107a following anti-PD1 and anti-CTLA-4. The frequency of CD8 + Tpex cells pre-ICB was also highest in this participant. Conclusion: In three PWH with cancer on ART, we found that ICB activated latent HIV and enhanced HIV-specific T cell function but with considerable variation. Abstract : Supplemental Digital Content is available in the text